2015
DOI: 10.3329/bccj.v3i2.25110
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Outcome of Diabetic Ketoacidosis: Experience at BIRDEM, Dhaka, Bangladesh

Abstract: Background: Diabetic ketoacidosis (DKA) is a medical emergency. It may be the presenting feature of diabetes mellitus, but more commonly DKA complicates diabetic patients during inter-current acute illness or if they become non-compliant to anti-diabetic medications. Early detection and treatment of DKA including underlying cause is important in determining outcome.Objectives: To describe the demographic characteristics, presentations, precipitating factors and outcome of DKA.Methods: This cross-sectional stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…The same result was found in a research done in Nigeria (22).On the contrary abdominal pain appeared to be the most common presenting symptoms in a cross-sectional study conducted in Egypt (17) and vomiting was the major clinical presentation in a research done at Saudi Arabia (12). Nausea was the most common presentation in a study done in India (2015) (23)and Bangladesh (24). The frequent occurrence of the aforementioned symptoms in DKA patients could be due to the fact that the presence of insulin deficiency results in hyperglycemia which in turn causes an osmotic diuresis.…”
Section: Discussionsupporting
confidence: 70%
“…The same result was found in a research done in Nigeria (22).On the contrary abdominal pain appeared to be the most common presenting symptoms in a cross-sectional study conducted in Egypt (17) and vomiting was the major clinical presentation in a research done at Saudi Arabia (12). Nausea was the most common presentation in a study done in India (2015) (23)and Bangladesh (24). The frequent occurrence of the aforementioned symptoms in DKA patients could be due to the fact that the presence of insulin deficiency results in hyperglycemia which in turn causes an osmotic diuresis.…”
Section: Discussionsupporting
confidence: 70%
“…Nearly three-quarters of the patients who were admitted with DKA did not develop complications associated with the disease. Majority (13.45%) of our patients were complicated with AKI, which is considered low as compared to a study conducted in Bangladesh showing that 29.5% of their patients developed AKI [16]. This variation could be explained by the severity of dehydration and how early fluid replacement is initiated.…”
Section: Discussionmentioning
confidence: 57%
“…A similar incidence of symptoms has been reported in previous studies done by Munro et al, Umpierrez et al, and Adhikari et al 9,19,20 A similar study from Bangladesh on 200 DKA T2DM patients also reported nausea and vomiting (63%), polyuria (43%), polydypsia (42.5%), fever (29%) and abdominal pain (28%) as the most common presenting symptoms. 21 Present study has revealed that DKA patients were having more than one precipitating factor like 53% who had poor compliance also had infection like pneumonia (24%) and UT I(22%). DKA patients also presented with stroke (7%) and MI (6%) as the precipitating factors.…”
mentioning
confidence: 71%